Mobile apps and coproduction: investigating the performance of municipal public service delivery - Teo, Kenneth Kang Sheng (Nanyang Technological University, 2017)
Current literature on 311 systems focuses mostly on citizen participation, with little empirical research on the performances of the municipal governments. This study aims to empirically investigate the effect of different 311 reporting channels on Boston public agencies’ performances in case resolution. 335,639 cases were analysed from Boston’s open data. Descriptive statistics provided a characterisation of overdue cases. Analysis of variance (ANOVA) and Welch test were used to test for mean differences across channels in time difference between target benchmarks and actual time taken for case resolution. Findings revealed that agencies often met target benchmarks for cases reported via the mobile app, yet took the longest on average to resolve each case. Innovation needs to be met with effective application in order to leverage on technological advances to advance public service delivery. Future research can build on this study to further develop evidence-based public policy making in smart cities.